2020
DOI: 10.1016/j.ensci.2020.100257
|View full text |Cite
|
Sign up to set email alerts
|

Prescription pattern of anti-Parkinson's disease drugs in Japan based on a nationwide medical claims database

Abstract: Introduction Parkinson's disease (PD) treatment should follow guidelines and be tailored to each patient. Large database analyses can provide insights into prescribing patterns. Methods Retrospective, cross-sectional study of patients (≥30 years) with PD diagnosis (ICD-10; schizophrenia/cerebrovascular disease excluded) using health insurance claims data (April 2008–December 2016) from the Japan Medical Data Vision database. Prescription patterns of anti-PD drugs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…In episodes in which levodopa was prescribed, in any of its forms (associated either with carbidopa or benserazide), a higher number of commission errors was evidenced (≈90% of medication errors detected). This could be explained by multiple factors: (i) On the one hand, levodopa is the most prescribed antiparkinsonian drug for the management of PD, [31][32][33] thus the odds of finding more errors in PD patients treated with this drug are higher. (ii) On the other hand, it is the most suitable antiparkinsonian drug to individualize according to a patient's clinical needs, due to the numerous liberation (immediate or extended) and dosage forms available.…”
Section: Discussionmentioning
confidence: 99%
“…In episodes in which levodopa was prescribed, in any of its forms (associated either with carbidopa or benserazide), a higher number of commission errors was evidenced (≈90% of medication errors detected). This could be explained by multiple factors: (i) On the one hand, levodopa is the most prescribed antiparkinsonian drug for the management of PD, [31][32][33] thus the odds of finding more errors in PD patients treated with this drug are higher. (ii) On the other hand, it is the most suitable antiparkinsonian drug to individualize according to a patient's clinical needs, due to the numerous liberation (immediate or extended) and dosage forms available.…”
Section: Discussionmentioning
confidence: 99%
“…]90% of medication errors detected). This could be explained by multiple factors: i) On the one hand, levodopa is the most prescribed antiparkinsonian drug for the management of PD [30][31][32], thus the odds of finding more errors in PD patients treated with this drug are higher. ii) On the other hand, it is the most suitable antiparkinsonian drug to individualize according to a patient's clinical needs, due to the numerous liberation (immediate or extended) and dosage forms available.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Japanese research reported that levodopa is most commonly prescribed, followed by non-ergot dopamine agonists (DAs), both as monotherapy and in combination with levodopa. [6][7][8] In our previous study using a Japanese claims database, a preference change between levodopa monotherapy and combination therapy with DAs was observed between 2010 and 2017. 9 This change might be associated with the publication of the 2011 Japanese guidelines, which recommend DAs as the initial treatment in patients with PD.…”
Section: Introductionmentioning
confidence: 98%
“…Dopamine replacement therapy, used to ameliorate motor symptoms, remains the standard treatment for patients with PD since levodopa was introduced in the 1960s, 4,5 despite the development of new medications with various action mechanisms and effects. Recent Japanese research reported that levodopa is most commonly prescribed, followed by non‐ergot dopamine agonists (DAs), both as monotherapy and in combination with levodopa 6–8 . In our previous study using a Japanese claims database, a preference change between levodopa monotherapy and combination therapy with DAs was observed between 2010 and 2017 9 .…”
Section: Introductionmentioning
confidence: 99%